Race-making, religion and rights in the post-colony: unmasking the pathogen in assembling a Hindu nation. Issue 4 (December 2022) - Kapur, Ratna
Abstract: This paper intervenes in critical socio-legal/post-colonial scholarship on human rights directed at how religion is constitutive of race and shapes who and what is regarded as 'human' and entitled to rights. It focuses on the Indian post-colony and legal persecution of the Tablighi Jamaat, a global, quietest Islamic movement, by the Hindu Right government during the Covid pandemic. It analyses how religion structures race in Hindu nationalist discourse to transform the Muslim into a perpetual outsider and an existential and epistemic threat to the Hindu nation and rights of the Hindu racial majority. The discussion connects to the epistemic anxiety generated by the alternative worldviews presented by this racialised 'Other' that shape legal consciousness and rights interventions globally. In complicating how anti-Muslim racism and Islamophobia are integral to the transnational histories of race and race-making, the analysis triggers a rethinking of human rights interventions and the epistemological closures they enact.